Modeling and controller design for an inverted pendulum system - Nasir, Ahmad Nor Kasruddin (2007)
This paper presents the simulation study of several control strategies for an inverted pendulum system. The goal is to determine which control strategy delivers better performance with respect to pendulum’s angle and cart’s position. The inverted pendulum represents a challenging control problem, which continually moves toward an uncontrolled state. Three controllers are presented i.e. proportional-integral-derivative (PID), linear quadratic regulator (LQR) for controlling the linear system of inverted pendulum and fuzzy logic controller (FLC) for controlling the non-linear system of inverted pendulum model. Simulation study has been done in Simulink shows that LQR produced better response compared to PID and FLC control strategies and offers considerable robustness.